c-d=f

Simple and best practice solution for c-d=f equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for c-d=f equation:


Simplifying
c + -1d = f

Solving
c + -1d = f

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add 'd' to each side of the equation.
c + -1d + d = d + f

Combine like terms: -1d + d = 0
c + 0 = d + f
c = d + f

Simplifying
c = d + f

See similar equations:

| 10x/x-6-60/x-6 | | 27x^2/3 | | =7x+5(1-x) | | 6(q-3)=-4(q+2) | | 5=10z+2(-7/2z-1) | | 2x-2=6x+1 | | 2p=km-t | | 3(x-4)=-1/2(24-6x) | | x-(5-3x)=7x*4 | | -5p=100 | | (19x-5)+(x+7)= | | 72*3/2 | | 1.5+2.5x+x=25 | | 3x^3-6x^2-75x+150=0 | | 5/2x=35-x | | 4r-8=24 | | -2=4y+x | | 5=13z-(z-1) | | 7x+2(7x+16)=179 | | 16/4=2u | | (x^(7/2))^(3/7)=8 | | 9x+4-3x=36 | | 3x+5+4x-12=15x-27 | | -2x+10=12-3x | | 1-4(u-1)=0 | | 4y-4/8+26/2=1/4 | | 2x^3+4x^2-3x=0 | | 2+9p-3p=14 | | 8+((12+5)*4)/2 | | 4/3+y/2=5/2 | | 2x^4+x^3-21x^2=0 | | x^2y=x^2-3y-1 |

Equations solver categories